Quantification of Resveratrol in Different Parts of Solid Pinotage Winery Waste: Investigating the Variance Between Consecutive Harvests - Kriel, C.; Pott, R.W.M. (South African Journal of Enology and Viticulture, 2020)
Resveratrol is phenolic compound that is produced by several plant species as a protection mechanism against biotic and abiotic stress. Resveratrol is currently being investigated as nutraceutical supplement, and there is a market value for the compound. The aim of this work was to investigate, through consecutive harvests the variability of solid winery waste as a source of resveratrol as an antioxidant supplement. In this study the different parts of Pinotage solid winery waste from a 2018 and 2019 harvests were investigated as a possible resveratrol source. From the comparison of the different sources over time it was found that the 2019 Pinotage stems contained a maximum of 73 ± 4.3 μg/g resveratrol. Variable resveratrol concentrations were noted between consecutive harvests, indicating a variability in productivity. Furthermore, resveratrol distribution throughout the plant was variable, with the canes and stems having the highest concentrations. Nonetheless, it was concluded that Pinotage solid winery waste can be used as a possible source of resveratrol. The findings in this paper provide information about the extractable resveratrol and total phenolic content of different parts of Pinotage solid winery waste and the variability of resveratrol content both within the plant, and between harvests.